Management Information System Factors for Educators and Education Personnel on Educator Performance - Khairul Anwar (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this study was to determine the factors in the Management Information System for Educators and Education Personnel on the performance of educators. Quantitative research methods with research models take variables from previous studies. Primary data are taken from distributing questionnaires to educators and getting 73 respondents. The analysis uses the SEM-PLS (Structural Equation Model-Partial Least Square) method using the SmartPLS application. The results of this study indicate that the variables of information quality, system use, and user satisfaction have a significant effect on the performance of educators. From this research, it is also known that the use of the system is the biggest factor in influencing the performance of educators. This research can be used as material in making strategies to improve the performance of Madrasah Aliyah educators in Cipondoh District generally for other Madrasas, and still be able to maintain the performance of existing educators.